Використання методу LoRA для адаптації моделей Stable Diffusion - Ішу, А. О. (ХНУРЕ, 2025)
The article is devoted to the LoRA (Low-Rank Adaptation) method for adapting Stable Diffusion models. The basic principles of this work are reviewed, looking at the mechanism for making low-level changes in the parameters of the model to change the payment costs. The key advantages of LoRA are analyzed, such as efficiency, flexibility and ease of integration, as well as possible shortcomings associated with it.
Keywords: метод LoRA; адаптація моделей Stable Diffusion